Citrus Research, Development and Biotechnology - Sarwar Khan, Muhammad; Ahmad Khan, Iqrar (IntechOpen, 2021)
Citrus is an extensively produced fruit crop and is cultivated predominantly in tropical and subtropical regions of the world. The Citrus genus consists of a variable number of species due to the admixture of wide morphological diversity, intra- and interspecific sexual compatibility, apomixis, and spontaneous mutations. Citrus fruits are highly nutritious and beneficial for health due to the presence of bioactive compounds that have antioxidant, antitumor, anti-inflammatory, and blood clot-inhibiting characteristics. This book describes the citrus plant and its nutrients, nutritional value, and nutraceutical applications, as well as related biotic and abiotic challenges in its cultivation. Chapters cover such topics as citrus genealogy, production, and crop management; milestones achieved in citrus improvement; importance of weather conditions in cropping systems; effects of changing climate on citrus; and much more.